Eine Klimakarte der Rheinlande - Böhm, Hans (ERDKUNDE, 1964)
The maps of the mean annual precipitation, mean actual annual, January and July temperatures of the climatic atlases of the States of the Federal Republic of Germany were used jointly in producing by graphical synthesis this map of the climatic elements of the Rhineland 1 : 1 million (map on left). The critical values of the original isotherm maps were retained, those of the precipitation maps were reduced to 500, 600, 700, 900, 1200 and 1400 mm. and over. Combinations of climatic elements, typical for the Rhinelands, emerge clearly from the key arranged in the form of a system of coordinates. By means of hygrothermical values the combinations of annual temperature and precipitation can be read off the ordinate and the January and July temperature combination off the abscissa. In the map of climatic provinces (on the right) an attempt has been made to arrange typical local climatic types and to establish climatic provinces and sub provinces.